Broyden's Method for Solving Fuzzy Nonlinear Equations - Amirah Ramli; Mohd Lazim Abdullah; Mustafa Mamat (Advances in Fuzzy Systems)
Instead of using standard analytical techniques, like Buckley and Qu method, which are not suitable for solving a system of fuzzy nonlinear equations where the coefficient is fuzzy number, Broyden's method is proposed for solving fuzzy nonlinear equations. In this paper, an eight-step algorithm is used to solve fuzzy nonlinear equations. Two numerical examples are given to illustrate the proposed method.